2013
DOI: 10.1177/070674371305800604
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Panic-Focused Psychodynamic Psychotherapy into Clinical Practice

Abstract: Objective: To determine the effectiveness of manualized panic-focused psychodynamic psychotherapy (PFPP) in routine care in Germany.Method: German psychoanalysts were trained according to the PFPP manual. Fifty-four consecutive outpatients with panic disorder (with or without agoraphobia) were randomly assigned in a 2:1 ratio to PFPP or cognitive-behavioural therapy (CBT) plus exposure therapy. Subjects (female 57.4%; mean age 36.2 years) had high rates of psychiatric (68.5%) and somatic (64.8%) comorbidity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 17 publications
1
40
0
1
Order By: Relevance
“…No additional RCTs fulfilling the inclusion criteria were identified by our search. In a recent RCT, no differences in outcome between PDT and CBT in panic disorder were found [76]. Remission rates at termination and follow-up were 44 and 50% for PDT and 61 and 56% for CBT.…”
Section: Methodsmentioning
confidence: 99%
“…No additional RCTs fulfilling the inclusion criteria were identified by our search. In a recent RCT, no differences in outcome between PDT and CBT in panic disorder were found [76]. Remission rates at termination and follow-up were 44 and 50% for PDT and 61 and 56% for CBT.…”
Section: Methodsmentioning
confidence: 99%
“…Some writers have theorized that patients with higher pretreatment insight may fare better in psychodynamic therapy than their low insight counterparts (see Barber, Muran, McCarthy, & Keefe, 2013). Indeed, Beutel et al (2013) found that patients with panic disorder who were higher in emotional awareness fared better in treatment. Closely related to the concepts of insight and emotional awareness, reflective functioning (RF) is defined as the ability to understand one's own and others'; behavior in terms of mental states (desires, intentions, feelings, and beliefs) (Fonagy, Target, Steele, & Steele, 1998).…”
Section: Theorized Moderators Of Response To Cbt and Pfppmentioning
confidence: 99%
“…In a small randomized, controlled trial (RCT), PFPP outperformed applied relaxation training (ART) in the reduction of panic symptoms and improvement in psychosocial functioning (Milrod, Leon, Busch, et al, 2007). Other supportive evidence of PFPP's efficacy comes from a study of its effectiveness in clinical practice (Beutel et al, 2013). …”
mentioning
confidence: 99%
“…In a direct comparison with CBT Beutel et al 2013), CBT was superior in some specific outcome parameters at the end of treatment. Longer follow-up studies for short-term psychodynamic psychotherapy are still lacking.…”
Section: Effectiveness and Sustainability Of Psychoanalytically Orienmentioning
confidence: 93%